PENGARUH PENGAWASAN, MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KLUNGKUNG - I Nyoman Ruspawan; Ida Ayu Putu Sri Widnyani (Locus, 2019)
The Klungkung Regency Communication and Information Office formed based on Regent of Klungkung Regulation Number 35 of 2016 concerning Position, Organizational Structure, Duties and Functions and Work Procedures for Regional Devices has the main task of carrying out regional household affairs in the field of Information Technology (IT).The objectives to be achieved in this study are (1) to determine the effect of supervision on the performance of Civil Servants at the Klungkung Regency Communication and Information Service, (2) to determine the effect of Motivation on the performance of Civil Servants at the Klungkung Regency Communication and Information Agency, (3 ) to find out the effect of Discipline on the performance of Civil Servants at the Communication and Information Office of Klungkung Regency, (4) To find out which variables are more dominant influence on the Performance of Civil Servants at the Communication and Information Office of Klungkung Regency, (5) To find out the variables of Supervision, Motivation and Discipline together - equally affect the Performance of Civil Servants at the Communication and Information Office of Klungkung Regency. The type of research used is a quantitative method with a population of all civil servants of the Communication and Information Office of Klungkung Regency being made as respondents, namely 31 people.Based on the results of the study concluded that supervision has a positive and significant effect on the performance of civil servants at 0.384 or 38.4%. Motivation has a positive and significant effect on the performance of civil servants at 0.365 or 36.5%. Discipline has a positive and significant influence onthe performance of civil servants at 0.342 or 34.2%. Supervision, motivation and discipline together explain the variable performance of civil servants at 71.8%,while the remaining 28.2% is explained by other variables not examined in this study or the research model.